The Beneficial Effect Of Yoga On Mental, Physical As Well As Spiritual Health On Human Being: A Brief Review - Kumar, Sujit; Raole, Vaidehi V; Bagul, Aparna; Patel, Jil (International Research Journal of Ayurveda & Yoga, 2020)
The key goals of Yoga are physical health, psychological wellbeing, social health, spiritual health, self knowledge or the knowledge of the Divine within us. These goals are achieved through love and help for all living beings, respect for all times, protection of nature and therefore of the environment, a peaceful state of mind, a full vegetarian diet, pure thoughts and a positive lifestyle, physical, mental and spiritual practices, tolerance for all nations, cultures and religions. Pranayama is a vital, but little-known aspect of Yoga. Lifestyle Yoga can be a practice program consisting of eight stages of growth in the fields of physical, emotional, social and spiritual wellness. If the body is physically healthy, the mind is calm, concentrated, and tension is under control. This gives the opportunity to connect with loved ones and establish socially healthy relationships.